An Accuracy Assessment of an IoT-Based Monitoring System for Household Water Consumption in Estimating Volume and Usage Cost: Analisis Tingkat Akurasi Sistem Monitoring Konsumsi Air Rumah Tangga Berbasis IoT terhadap Estimasi Volume dan Biaya Pemakaian - Tunggadewi, Elsyea Adia; Nahdliyah, Sisca Dina Nur (Muhammadiyah University, Sidoarjo, 2025)
Water-use efficiency in the household sector is a crucial aspect in supporting the sustainability of water resources. Enhancing this efficiency requires a monitoring system capable of accurately measuring consumption volume and precisely estimating usage costs. A relevant approach in this context is the implementation of Internet of Things (IoT)-based technology, which enables real-time data acquisition and transmission through smart water meter devices. This study aims to evaluate the accuracy of an IoT-based household water consumption monitoring system in estimating usage volume and calculating cost. The method involves a comparison between actual water flow data and system measurements, as well as an analysis of the discrepancy between actual costs and cost estimates produced by the application. Experimental results indicate an average deviation of 9.12% between the actual and measured volume. In contrast, the cost estimation demonstrates a very high level of accuracy, with a maximum discrepancy of only IDR 1 compared to the actual cost. These findings indicate that the system performs reliably in estimating cost, although some inaccuracies remain in volume measurement. Overall, the system demonstrates considerable potential as an effective and sustainable technological solution to support household water consumption management.